2018
DOI: 10.3390/molecules24010049
|View full text |Cite
|
Sign up to set email alerts
|

Less Exploited GPCRs in Precision Medicine: Targets for Molecular Imaging and Theranostics

Abstract: Precision medicine relies on individually tailored therapeutic intervention taking into account individual variability. It is strongly dependent on the availability of target-specific drugs and/or imaging agents that recognize molecular targets and patient-specific disease mechanisms. The most sensitive molecular imaging modalities, Single Photon Emission Computed Tomography (SPECT) and Positron Emission Tomography (PET), rely on the interaction between an imaging radioprobe and a target. Moreover, the use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 218 publications
(271 reference statements)
1
11
0
Order By: Relevance
“…The biodistribution and metabolism of the radiotracers are primarily dependent on the bioavailability and potential competitors in the organism. The total amounts of injected peptide and the resulting blood plasma concentrations in the biodistribution studies of the 64 Culabeled peptides were comparable with reported Ghrelin level in vivo (0.09-0.22 nM) [33][34][35] of lined rats.…”
Section: Comparing the Biodistribution Of 10b And 10c In Healthysupporting
confidence: 77%
See 1 more Smart Citation
“…The biodistribution and metabolism of the radiotracers are primarily dependent on the bioavailability and potential competitors in the organism. The total amounts of injected peptide and the resulting blood plasma concentrations in the biodistribution studies of the 64 Culabeled peptides were comparable with reported Ghrelin level in vivo (0.09-0.22 nM) [33][34][35] of lined rats.…”
Section: Comparing the Biodistribution Of 10b And 10c In Healthysupporting
confidence: 77%
“…Although widely studied as a promising drug target, our knowledge about Ghrelin signaling, behavior, dynamic interactions with its receptor and functional receptor expression in vivo is still limited and basic bioscientific research is warranted to further evaluate the safety and benefits of Ghrelin drug treatment in patients with cancer [31][32][33]. In vivo imaging of the Ghrelin receptor should help to improve our understanding of its mode of action and might become a powerful tool for diagnosis and drug development [26,34]. So far, only few groups tried to develop probes for PET and optical imaging of Ghrelin receptors [26,[35][36][37][38][39][40].…”
Section: Research Papermentioning
confidence: 99%
“…In addition, OTSA101-DTPA- 111 In and OTSA101-DTPA- 90 Y are humanized chimeric anti-Fzd10 antibodies (named OTSA-101) that are radiolabeled with Indium 111 and Yttrium 90, respectively. OTSA101-DTPA- 111 In is a promising Fzd10-targeted single-photon emission computed tomography (SPECT) imaging agent, while OTSA101-DTPA- 90 Y is a potent Fzd10-targeted agent for metastatic synovial sarcoma radiotherapy [ 420 , 421 ]. Salinomycin is an FDA-approved supplement in poultry feed and kills BCSCs selectively [ 424 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, approximately one third of clinically approved drugs target these receptors and a continuously increasing number of GPCR-targeting drug candidates are under clinical trials and under pre-clinical development [ 60 ]. Additionally, a rising trend of exploring GPCR in precision medicine for targeted therapy, diagnostics, and/or drug delivery has been reported as well [ 60 , 61 ]. Within this context, in this section, we discuss the most relevant GPCR that have been studied for the targeted-delivery of ruthenium and gold complexes into cancer cells, including the somatostatin receptors (SSTR), bombesin receptors (BBR), opioid receptors (OPR), and G protein-coupled estrogen receptors (GPER), all of them belonging to the Class A group.…”
Section: G Protein-coupled Receptors (Gpcr)mentioning
confidence: 99%